Beliefs about the uncontrollability of emotions and interpersonal needs as predictors of Suicide Crisis Syndrome - Colmenero-Navarrete, Lidia; Salguero-Noguera, José Martín; García-Sancho, Esperanza (Elsevier, 2025)
Suicide Crisis Syndrome (SCS) is an “acute” mental state characterized by intense cognitive and affective dysregulation which aims to explain the psychological processes occurring in the days or hours prior to suicide behavior. SCS has been shown to be able to predict suicide behavior, however, few studies have studied which variables predict it. In this study we examined the predictive role of beliefs about the uncontrollability of emotions and interpersonal needs on SCS. We used a sample of 276 participants (50,4% male), ranging in age from 18 to 77 years, who completed a 4-month follow-up study, to address our hypotheses. Results showed that emotional uncontrollability beliefs and perceived burdensomeness predicted SCS. Furthermore, the perception of burdensomeness at Time 1 mediated the link between uncontrollability beliefs at Time 1 and SCS at Time 2. Clinical implications of these results and future lines of research are discussed.
Keywords: Suicidio - Aspectos psicológicos; Síndromes; Suicide Crisis syndrome; Emotional uncontrollability beliefs; Thwarted belongingness; Perceived burdensomeness; Suicide behavior